1976
DOI: 10.1007/3-540-08004-x_308
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solutions of the triple-deck equations for laminar trailing-edge stall

Abstract: In this paper, we consider the problem of determining the effect of laminar boundary layers on the lift of thin wings in subsonic flow at high Reynolds numbers°The viscous flow about an airfoil at high Reynolds numbers is largely controlled by a strong local interaction between the boundary layer, wake, and external potential flow near the trailing edge. The standard (weak) interaction theory for laminar flows develops singularities in the second-order inviscid solution and is not uniformly valid at trailing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…This has been confirmed recently by Korolev (1989) who was able to extend the numerical solutions of the triple deck problem into the separated flow regime. According to these results the wall shear on the upper plate surface at x = 0-reaches a minimum value Tw(O-) = O for a = 0.47 in agreement with the estimate for incipient separation given by Chow and Melnik (1976). For larger values of a the boundary layer on the upper plate surfaces separates but reattaches upstream of the trailing edge so that Tw(O-) now increases with increasing angle of attack.…”
Section: (22)supporting
confidence: 86%
See 3 more Smart Citations
“…This has been confirmed recently by Korolev (1989) who was able to extend the numerical solutions of the triple deck problem into the separated flow regime. According to these results the wall shear on the upper plate surface at x = 0-reaches a minimum value Tw(O-) = O for a = 0.47 in agreement with the estimate for incipient separation given by Chow and Melnik (1976). For larger values of a the boundary layer on the upper plate surfaces separates but reattaches upstream of the trailing edge so that Tw(O-) now increases with increasing angle of attack.…”
Section: (22)supporting
confidence: 86%
“…The most simple example is provided by the flow of an incompressible fluid past a flat plate at incidence. If the angle of attack a* is small, the flow ne ar the trailing edge can stiH be investigated by means of triple deck theory, Brown and Stewartson (1970), Chow and Melnik (1976). In contrast to the case of aligned flow, however, two triple decks, one on the suction si de and one on the pressure side of the plate, have to be considered separately.…”
Section: (22)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is the flow past a thin airfoil at an angle a* of incidence, the airfoil being suitably rounded at the leading edge to prevent separation there and having a sharp trailing edge. Chow and Melnik [3] have shown that as a* increases a solution for the trailing-edge region is only possible if a< 0.47, where a* = >...9/ 8 R-…”
Section: Introductionmentioning
confidence: 99%